On the Issue of Oil. (c2017) - El-Chammas, Diana (2017)
Tensions between Lebanon and Israel have lately been on the rise due to the two countries’ opposing proposals for the delineation of their respective Exclusive Economic Zones (EEZ), and the resulting overlapping maritime area. As no peace treaty or diplomatic relations exist between the two states, no agreement can directly be made on the boundaries delimitation. This thesis analyzes the contested points between the two delineated EEZ proposals and their legal ramifications, the complications in settling such a dispute and the factors influencing that process including the Arab-Israeli historical conflict and recent flash-points between Lebanon and Israel. The research which draws on existing research and expert analysis offers ways to look at the future prospects for peace between Lebanon and Israel.